Analysis for Stabilization of Soil Slope in Silty Soil with Replacement of Soil Cement - Muhammad Zohair; Dildar Ali Mangnejo; Naeem Mangi (Civil Engineering Journal, 2019)
The slope instability may result due to change in stress conditions, rise in groundwater and rainfall. Similarly, many slopes that have been stable for many years may suddenly fail due to loss of soil shear strength, and external forces. This is a crucial problem as it may destroy buildings, damage roads, and even leads to loss of human life. So it is imperative to understand failure mechanism and adopt safety measures to prevent such failures. The objective of this study is to analyze the slope at different angles (at 300, 350, 450 & 600 ) in silty soil and propose a method to stabilize it. The proposed methods to stabilize the existing slope are replacing soil-cement (7% by weight) by vertical layering and layering along the slope. Limit equilibrium method was used to analyze the slopes. The existing slopes were likely to be failed because values of minimum FOS was computed less than 1.5. The FOS improved significantly after replacing soil cement by both methods. Among the two methods, it was revealed that the layering along slope method of soil replacement was most economical and easy to be executed at the site.